On the relation between Fourier and Leont’ev coefficients with respect to Smirnov spaces - Forster, B. (Український математичний журнал, 2004)
Yu. Mel’nik showed that the Leont’ev coefficients Κ f (λ) in the Dirichlet series 2n/(n+1) 2 of a function f ∈E p (D), 1 < p < ∞, are the Fourier coefficients of some function F ∈L p , ([0, 2π]) and that the first modulus of continuity of F can be estimated by the first moduli and majorants in f. In the present paper, we extend his results to moduli of arbitrary order. Ю. І. Мельник показав, що коефіцієнти Леонтьєва 2n/(n+1) 2 для функції f ∈E p (D), 1 < p < ∞, є коефіцієнтами Фур'є для деякої функції F∈Lp,([0,2π]) і що перший модуль неперервності F можна оцінити першими модулями та мажораптами в f. У даній статті його результати поширено на модулі довільного порядку.